High versus low intensity interventions for perinatal depression delivered by non-specialist primary maternal care providers in Nigeria: a cluster randomized controlled trial: (the EXPONATE trial) (2019)
Contextually appropriate interventions delivered by primary maternal care providers (PMCPs) might be effective in reducing the treatment gap for perinatal depression. Aim To compare high-intensity treatment (HIT) with low-intensity treatment (LIT) for perinatal depression. Method Cluster randomised clinical trial, conducted in Ibadan, Nigeria between 18 June 2013 and 11 December 2015 in 29 maternal care clinics allocated by computed-generated random sequence (15 HIT; 14 LIT). Interventions were delivered individually to antenatal women with DSM-IV (1994) major depression by trained PMCPs. LIT consisted of the basic psychosocial treatment specifications in the World Health Organization Mental Health Gap Action Programme – Intervention Guide. HIT comprised LIT plus eight weekly problem-solving therapy sessions with possible additional sessions determined by scores on the Edinburgh Postnatal Depression Scale (EPDS). The primary outcome was remission of depression at 6 months postpartum (EPDS < 6). Results There were 686 participants; 452 and 234 in HIT and LIT arms, respectively, with both groups similar at baseline. Follow-up assessments, completed on 85%, showed remission rates of 0% with HIT and 66% with LIT: risk difference 4% (95% CI −4.1%, 12.0%), adjusted odds ratio 1.12 (95% CI 0.73, 1.72). HIT was more effective for severe depression (odds ratio 2.29; 95% CI 1.01, 5.20; P = 0.047) and resulted in a higher rate of exclusive breastfeeding. Infant outcomes, cost-effectiveness and adverse events were similar. Conclusions Except among severely depressed perinatal women, we found no strong evidence to recommend high-intensity in preference to low-intensity psychological intervention in routine primary maternal care.